2017
DOI: 10.1161/strokeaha.116.015565
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis, Tobacco, Alcohol Use, and the Risk of Early Stroke

Abstract: Background and Purpose-Current knowledge on cannabis use in relation to stroke is based almost exclusively on clinical reports. By using a population-based cohort, we aimed to find out whether there was an association between cannabis use and early-onset stroke, when accounting for the use of tobacco and alcohol. Methods-The cohort comprises 49 321 Swedish men, born between 1949 and 1951, who were conscripted into compulsory military service between the ages of 18 and 20. All men answered 2 detailed questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 28 publications
1
55
0
Order By: Relevance
“…The misclassification bias corrected risk ratio was calculated under the assumption of sensitivity of visit for concussion follows a uniform distribution ranging from 80% to 100% (i.e., 80% of patients will visit a doctor) and the specificity of concussion visit follows a uniform distribution ranging from 50% to 100% (i.e., 50% of visits were over-diagnosed as concussion). The median smoking-adjusted stroke incidence rate ratio was calculated under the assumption of a prevalence ranging from 15% to 18% and risk ratio for any stroke episode for smokers ranging from 1.61 to 9.06 [18]. Both bias corrected and smoking-adjusted incidence rate ratio were compared to observed incidence rate ratios to quantify the effect of bias.…”
Section: Methodsmentioning
confidence: 99%
“…The misclassification bias corrected risk ratio was calculated under the assumption of sensitivity of visit for concussion follows a uniform distribution ranging from 80% to 100% (i.e., 80% of patients will visit a doctor) and the specificity of concussion visit follows a uniform distribution ranging from 50% to 100% (i.e., 50% of visits were over-diagnosed as concussion). The median smoking-adjusted stroke incidence rate ratio was calculated under the assumption of a prevalence ranging from 15% to 18% and risk ratio for any stroke episode for smokers ranging from 1.61 to 9.06 [18]. Both bias corrected and smoking-adjusted incidence rate ratio were compared to observed incidence rate ratios to quantify the effect of bias.…”
Section: Methodsmentioning
confidence: 99%
“…Two prospective studies examined the effect of marijuana exposure on stroke and transient ischemic attack (35, 36). One study (moderate ROB), based on CARDIA, reported that marijuana was not associated with stroke (adjusted HR, 0.65 [CI, 0.16 to 2.66]; P = 0.76); however, the exposure was minimal (median lifetime of 0.51 marijuana-years or 50 times) and the population was young and healthy (35).…”
Section: Resultsmentioning
confidence: 99%
“…They were followed until age 59 to assess the initial occurrence of stroke. No association between cannabis use and stroke (HR, 0.93 [CI, 0.34 to 2.57]) was identified, but the study was limited by potential misclassification of the exposure, given that it was not reassessed over 25 years of follow-up and adjustment for baseline characteristics was inadequate (36). …”
Section: Resultsmentioning
confidence: 99%
“…Posterior TPAs arise from the superior, posterior, or posterosuperior surfaces of P1. Their morphological diversity and branching patterns, with multiple variations and complex courses, were subject of autopsy studies [ 7 17 ] and structural imaging scans [ 18 37 ], respectively.…”
Section: Introductionmentioning
confidence: 99%